IDENTIFIKASI PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK PEMBANGUNAN SEKOLAH XYZ, DI KECAMATAN HAMPARAN PERAK, KABUPATEN DELI SERDANG, SUMATERA UTARA: EVALUASI PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK KONSTRUKSI GEDUNG SEKOLAH DI KABUPATEN DELI SERDANG - Rumiris Simamora; Putri Radhika Meisya Br Barus Barus; Egi Heindrik Pandiangan; Josua Orlando Lingga4; Fiser Tampubolon5; Titonik Feberman Hia; yuni Yolanda (Fakultas Teknik Universitas Hamzanwadi, 2026)
The implementation of Occupational Health and Safety (OHS/SMK3) integrated with environmental management remains a challenge in construction projects, particularly due to inconsistent use of Personal Protective Equipment (PPE), limited distribution of safety signage, and potential hazards arising from high-risk work activities. These issues were identified in the XYZ School Construction Project located in Hamparan Perak District, Deli Serdang Regency, which involves various construction activities with significant risks to worker safety and environmental quality, such as dust, noise, and material waste. This study aims to analyze the level of OHS implementation and evaluate aspects that need improvement to minimize occupational accident risks and environmental impacts. The research method used is descriptive qualitative with an observational approach through direct field observations conducted over approximately three months, supported by documentation and literature review. Data were analyzed by classifying OHS aspects, including high-risk work activities, PPE usage, safety signage and facilities, work environment conditions, as well as supervision and work procedures. The results indicate that OHS implementation has generally been carried out adequately; however, several issues remain, including inconsistent PPE usage, uneven distribution of safety signage, and suboptimal control of environmental factors such as dust and noise. In conclusion, although most OHS standards have been met, improvements in PPE compliance, distribution of safety facilities, supervision, and environmentally oriented work practices are necessary to reduce accident risks and achieve a safer, healthier, and more sustainable construction environment.